The Routledge Handbook of Family Communication
DOI: 10.4324/9780203848166.ch17
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Child Communication During Adolescence

Abstract: To appear in: Vangelisti, A. L. (Ed.). Routledge Handbook of Family Communication (2 nd ed.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
144
2
4

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(159 citation statements)
references
References 48 publications
9
144
2
4
Order By: Relevance
“…This challenges the notion that parent-child communication frequency decreases over time due to adolescents seeking autonomy from their parents (Branje et al, 2012); however, this is also gender-dependent, because previous research has suggested that girls tend to communicate more frequently with their parents than do boys (Cumsille, Darling, & Martínez, 2010). …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This challenges the notion that parent-child communication frequency decreases over time due to adolescents seeking autonomy from their parents (Branje et al, 2012); however, this is also gender-dependent, because previous research has suggested that girls tend to communicate more frequently with their parents than do boys (Cumsille, Darling, & Martínez, 2010). …”
Section: Discussionmentioning
confidence: 88%
“…Youth can claim more autonomy from their parents by spending less time with them (Larson, Richards, Moneta, Holmbeck, & Duckett, 1996). Corresponding to this decrease in spending time with parents is the decrease in the frequency of parent-child communication (Branje, Brett, & Collins, 2012). However, there is variability in how parent-child communication and parental knowledge change over time.…”
Section: Introductionmentioning
confidence: 99%
“…Mother-adolescent dyads with more emotional rigidity seem to have difficulties expressing, adjusting, and regulating emotions during conflict interactions (23,25,28). They do not experience a supportive and safe context to discuss diverging views and opposing emotions (39), and are therefore less equipped to flexibly handle different emotional challenges (14). In general, these results suggest that conflict interactions between parents and adolescents are adaptive for relational development when these interactions are characterized by the ability to switch flexibly between a range of emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Greater emotional variability in early adolescence was not related to concurrent maternal control but predicted a relative decrease in perceived maternal control in late adolescence. This corresponds to the idea that more parental control is considered normative in early adolescence , but from midadolescence, youth tend to see issues that were previously under parents’ jurisdiction as part of the personal domain; parents need to accommodate adolescents’ increasing need for autonomy and allow them to make decisions without informing parents .…”
Section: Conflict Interactions and Changes In The Parent–adolescent Rmentioning
confidence: 97%
“…Furthermore, adolescence is a developmental stage during which families and parent-adolescent relationships undergo significant change (e.g., Branje, Laursen, & Collins, 2012;Laursen & Collins, 2009;Mastrotheodoros, van der Graaff, Deković, Meeus, & Branje, 2018;Meeus, 2016). Adolescents strive for autonomy, often much earlier than parents are willing to grant it (e.g., Deković, Noom, & Meeus, 1997), which might be a reason for the increased tension between parents and adolescents (Laursen, Coy, & Collins, 1998).…”
Section: Interparental Conflict Management Strategies and Parent-adolmentioning
confidence: 99%